Non-coding RNA and reprogrammed mitochondrial metabolism in genitourinary cancer - Thirunavukkarasu, Sandiya; Banerjee, Shouryarudra; Tantray, Ishaq; Ojha, Rani (Frontiers in Genetics, 2024)
Non-coding ribonucleic acids (ncRNAs) have been recently shown to contribute to tumorigenesis by mediating changes in metabolism. ncRNAs act as key molecules in metabolic pathways regulation. The dysregulation of ncRNAs during cancer progression contributes to altered metabolic phenotypes leading to reprogrammed metabolism. Since ncRNAs affect different tumor processes by regulating mitochondrial dynamics and metabolism, in the future ncRNAs can be exploited in disease detection, diagnosis, treatment, and resistance. The purpose of this review is to highlight the role of ncRNAs in mitochondrial metabolic reprogramming and to relate their therapeutic potential in the management of genitourinary cancer.